PEMBERDAYAAN GURU HONORER MELALUI LAUNCHING SOBAT PINTAR AKADEMIA (SOPIA) DAN APLIKASI MEDIA PEMBELAJARAN SEBAGAI UPAYA PENINGKATAN EKONOMI DI MASA PANDEMI COVID-19 - Suttrisno; Eko Arief Cahyono; Yogi Prana Izza (Mafaza : Jurnal Pengabdian Masyarakat, 2022)
Honorary teachers and school children are one of the assets owned by the people of Kacangan Village. The Covid-19 outbreak has changed and hampered all activities in Kacangan Village, including affecting the community's economy, including the education sector. Therefore, in community service activities in Kacangan Village, in collaboration with partners, in this case Baznas Bojonegoro, SDN Kacangan 1 and SDN Kacangan 2, held a learning media application workshop and launched a friend of smart academics (SOPIA). In this community service activity, the Asset Based Community Development (ABCD) method is used, which is a community development concept based on local assets to overcome problems in the area. The results of this community service activity were a learning media application workshop and the launching of Sobat Pintar Akademia (SOPIA), namely all educators in Kacangan used this learning media and students in Kacangan received knowledge well and the students were very enthusiastic when participating tutoring, as well as mentors who will provide guidance to students so that they can improve the economy of the Kacangan Village community during the Covid 19 pandemic.